Transformational Leadership, Psychological Empowerment, and Innovative Work Behavior of Frontline Employees in the Public Sectors: Empirical Evidence from North Sumatera, Indonesia - inaga, Anggun Tiur Ida S; Lumbanraja, Prihatin; Sadalia, Isfenti; Silalahi, Amlysh Syahputra (Journal of International Conference Proceedings, 2020)
The purpose of this paper is to investigate the impact of transformational leadership (TL) and psychological empowerment (PE) on innovative work behavior (IWB) of frontline employees at public sector in North Sumatera. This study examines the effects of PE as a moderator on the relationship between transformational leadership and innovative work behavior (IWB). The data were collected from 786 frontline employees through an online survey. Partial least square structural equation modeling analysis by the bootstrap method were used for the data analysis. Results indicated that TL and PE have positive influence on innovative work behavior, however specifically, the result showed that PE does not moderates on the relationship between TL and IWB of frontline employees in North Sumatera.